Car dealer escapes the gallows: Grief: Father distraught after accused was found not guilty of daughter's murder - Povera, Adib (New Straits Times, 2013)
A CARPENTER caused a stir when he threatened to jump off the balcony of the double-storey state court complex here yesterday after the High Court found a car dealer not guilty of the murder of his daughter seven years ago.